1973
DOI: 10.1099/00221287-75-1-179
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Expression for Oxygen-induced Death in Dehydrated Bacteria

Abstract: A mathematical expression for oxygen-induced death of dehydrated bacteria is reported. Data in the literature for Serratia marcescens SUK were analysed and the expression describes viability changes over a range of lo4, oxygen concentration effects over a range of 400 and the effect of time up to 3 h. The expression should apply to the oxygen-induced death of other dehydrated bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The results presented in Fig. 1 through 4 and were analyzed by a curve-fitting procedure as n of described before (15), but in terms of equation 9 . at (see Appendix):…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented in Fig. 1 through 4 and were analyzed by a curve-fitting procedure as n of described before (15), but in terms of equation 9 . at (see Appendix):…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli B, E. coli commune, and E. coli Jepp were grown, aerosolized as a suspension in distilled water, sampled, and assayed as previously (6,7), except that aerosols were stored in nitrogen (>99.9%) at a smaller number of relative humidities (RH) and were sampled at storage times of 2, 5, 10, 15, 20, 25, and 30 min. Semliki forest virus (SFV) was studied as before (3), except that aerosols were generated from a suspension of the virus in medium 199 + 10% (vol/vol) calf serum and were stored at a larger number of RH values and for shorter periods of time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reation rate with each site is of a first order, but the observed overall rate is the sum of all the separate rates and is changing with exposure time. Cox et al (1973) tried to fit a mathematical expression for oxygen-induced death in dehydrated bacteria (freeze-dried and aerosolized). They suggested survival equations based on reaction rates of oxygen, first with a carrier molecule-X, and then with the sensitive substance-A.…”
Section: Pseudomonas Syringaementioning
confidence: 99%
“…Cox and Heckly (12) and Cox et al (10) found that the toxic action of oxygen upon freeze-dried Serratia marcescens 8UK followed first-order kinetics at low concentrations of oxygen (i.e. logarithm of the viability at a given storage time was directly proportional to oxygen concentration) and zero order at high oxygen concentration (i.e.…”
Section: Introductionmentioning
confidence: 98%